Recurrence, progression and cancer-specific mortality according to stage at re-TUR in T1G3 bladder cancer patients treated with BCG: not as bad as previously thought - Palou, J; Pisano, F; Sylvester, R; Joniau, S; Serretta, V; Larré, S; Di Stasi, S; van Rhijn, B; Witjes, A J; Grotenhuis, A; Colombo, R; Briganti, A; et al. (World journal of urology, 2018)
PURPOSE: The goals of transurethral resection of a bladder tumor (TUR) are to completely resect the lesions and to make a correct diagnosis to adequately stage and treat the patient. Persistent disease after TUR is not uncommon and is why re-TUR is recommended in T1G3 patients. When there is T1 tumor in the re-TUR specimen, very high risks of progression (82%) have been reported. We analyze the risks of recurrence, progression to muscle-invasive disease and cancer-specific mortality (CSM) according to tumor stage at re-TUR in T1G3 patients treated with BCG. METHODS: In our retrospective cohort of 2451 T1G3 patients, 934 patients (38.1%) underwent re-TUR. 667 patients had residual disease (71.4%): Ta in 378 (40.5%), T1 in 289 (30.9%) patients. Times to recurrence, progression and CSM in the three groups were estimated using cumulative incidence functions and compared using the Cox regression model. RESULTS: During a median follow-up of 5.2 years, 512 patients recurred. The recurrence rate was significantly higher in patients with a T1 at re-TUR (P < 0.001). Progression rates differed according to the pathology at re-TUR, 25.3% in T1, 14.6% in Ta and 14.2% in case of no residual tumor (P < 0.001). Similar trends were seen in both patients with and without muscle in the original TUR specimen. CONCLUSIONS: Patients with T1G3 tumors and no residual disease or Ta at re-TUR have better recurrence, progression and CSM rates than previously reported, with a CSM rate of 13.1 and a 25.3% progression rate in re-TUR T1 disease.
Keywords: Administration, Intravesical; Neoplasm Recurrence, Local; Re-transurethral resection of the bladder; adjuvancia imunologická; Cystectomy; senioři; Neoplasm Staging; Non-muscle invasive bladder cancer; Aged; Male; progrese nemoci; Retrospective Studies; lidé; reoperace; Urinary Bladder Neoplasms; Humans; retrospektivní studie; Cause of Death; cystektomie; Reoperation; aplikace intravezikální; Adjuvants, Immunologic; BCG Vaccine; lokální recidiva nádoru; mužské pohlaví; příčina smrti; Proportional Hazards Models; staging nádorů; následné studie; proporcionální rizikové modely; nádory močového měchýře; Recurrence; Disease Progression; ženské pohlaví; Follow-Up Studies; Female; Progression; BCG vakcína